Cultivating reading habit among secondary school students: The DEAR programme - Noorazaliza Izha, Haron (2009)
This study investigated on the effectiveness of the DEAR Programme in a secondary school. It aimed to discover whether the programme has successfully cultivated positive reading habit among students. It also identified the elements which contribute to the programme's success, and ways to improve. Semi-structured interviews were carried out with ten teachers and twenty-two students from forms one, two, and four of this school. Analysis revealed several themes: 1) freedom to choose reading materials, 2) environment, 3) time, 4) reading materials, 5) teachers' role, 6) involvement, 7) changes in the students' reading habits. 8) misconceptions of the DEAR Programme, and 9) suggestions for improvement. The DEAR Programme in this school has been successful in cultivating reading habit. However, the programme can be improved if elements of monitoring, clarity of information, and involvement of all members in the school are emphasized.